Pengaruh Kualitas Pelayanan, Tarif dan Fasilitas Terhadap Kepuasan Penumpang Bus BRT Trans Semarang (Studi Kasus: Penumpang Bus BRT Trans Semarang koridor II) - Amri Rifqi Azhari; Nawazirul Lubis; Ngatno Ngatno (Universitas Diponegoro, 2016)
The population density in the city of Semarang cause a variety of problems, one of which is the bottleneck. BRT Trans Semarang is one government program to tackle the issue. This study aims to determine the effect of quality of service, tariffs and facilities for passenger satisfaction Trans Semarang BRT corridor II. Data collection techniques used were interviews and questionnaires, while the sampling technique used purposive sampling with a sample size of 100. The data was analyzed through the validity, reliability, product moment correlation, coefficient of determination, simple linear regression, multiple linear regression, t test and F. test quantitative data were analyzed using SPSS version 20. The results showed that the quality of service, rates and facilities significant effect on passenger satisfaction BRT corridor II Trans Semarang partially. And quality of service, rates and facilities significant effect on passenger satisfaction Trans Semarang BRT corridor II simultaneously. Trans Semarang service quality BRT Corridor II should be improved. Enhancement can be done by increasing the number of buses, improve the quality of shelter, improving the quality of human resources through training and extending the hours of service that passengers feel comfortable and satisfied when using BRT transportation services Trans Semarang.